2021
DOI: 10.1111/1750-3841.15893
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and antioxidant activity of PCL‐microencapsulated olive leaves polyphenols and its application in yogurt

Abstract: Polycaprolactone (PCL)was used via double emulsion/solvent evaporation technique for the encapsulation of polyphenols olive leaves (OLs) extracts. In this study, the PCL‐microcapsules loaded with OLs polyphenols extract powder were characterized by scanning electron microscopy and fourier transform infrared spectrometry analysis. Their total phenolic (TPC), total flavonoid (TFC) contents, and antioxidant activities (DPPH, FRAP, and ABTS), and polyphenols stability were measured after oral, gastric, and intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 49 publications
1
7
2
Order By: Relevance
“…The highest decrease in viscosity was observed on the 14th day of storage ( Figure 2 ), which also corresponded to the observed decrease in pH values ( Figure 1 ) detected during the first 14 days. Such trends were also reported by Cho et al [ 8 ] and El-Messery et al [ 11 ], who also detected a decrease in viscosity of all samples during 14 days of cold storage. After that period, viscosity started to increase, reaching at the end almost identical values as on the first day for some samples (control, OLE 1.5%, and OLE 3%) ( Figure 2 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The highest decrease in viscosity was observed on the 14th day of storage ( Figure 2 ), which also corresponded to the observed decrease in pH values ( Figure 1 ) detected during the first 14 days. Such trends were also reported by Cho et al [ 8 ] and El-Messery et al [ 11 ], who also detected a decrease in viscosity of all samples during 14 days of cold storage. After that period, viscosity started to increase, reaching at the end almost identical values as on the first day for some samples (control, OLE 1.5%, and OLE 3%) ( Figure 2 ).…”
Section: Resultssupporting
confidence: 88%
“…Some authors have already studied the possibilities of adding OLE to yoghurt, in order to examine the options of supplementation (liquid, concentrated, powdered, encapsulated, pure oleuropein), as well as to increase its shelf life and/or functionality [ 6 , 8 , 9 , 10 ]. In these studies, the used extracts were usually obtained by boiling in hot water [ 6 , 10 ] or extracted from organic solvents such as ethanol, subsequently subjecting them to further processing operations such as freeze-drying, evaporation, or encapsulation [ 8 , 10 , 11 ], to obtain a higher concentration of active compounds to be added into yoghurt. From the perspective of developing new products, employment of so many intermediate steps might not simply appear unpractical but also expensive for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…According to the method of El-Messery et al ( 23 ), the syneresis rate of yogurt was calculated using the following Equation (3):…”
Section: Methodsmentioning
confidence: 99%
“…The lower amounts released during all stages of digestion indicated that these compounds were held within the capsules and were not exposed to the digestion fluids. This is due to the low solubility of the encapsulation material at low pH, which prevents the phenols release in the acidic environment . Thus, the encapsulated samples in this system were less bioaccessible and would most likely pass through the colon without being absorbed in the upper gastric tract.…”
Section: Bioaccessibility Of Lignansmentioning
confidence: 99%